COVID-19 Is Changing Our Understanding of the Neuroscience of Viral Infections: What We Can Do to Prepare for the Future? - Kore Kai Liow; Jason Viereck (MDPI AG, 2022)
In the approximately two years since the emergence of COVID-19 (Coronavirus Disease 2019) myriad neurological symptoms have been reported that are seemingly unrelated to each other [...]